2010
DOI: 10.1038/onc.2010.357
|View full text |Cite
|
Sign up to set email alerts
|

CIP2A mediates effects of bortezomib on phospho-Akt and apoptosis in hepatocellular carcinoma cells

Abstract: Previously, we reported that Akt inactivation determines the sensitivity of hepatocellular carcinoma (HCC) cells to bortezomib. In this study, we report that cancerous inhibitor of protein phosphatase 2A (CIP2A), a cellular inhibitor of protein phosphatase 2A (PP2A), mediates the apoptotic effect of bortezomib in HCC. Silencing PP2A by small interference RNA (siRNA) abolishes bortezomib-induced down-regulation of phospho-Akt and apoptosis. Bortezomib increases PP2A activity in sensitive HCC cells, including Sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
128
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(139 citation statements)
references
References 25 publications
10
128
0
1
Order By: Relevance
“…These results suggest that MYC contributes to the CIP2A-mediated stimulation of HeLa cell colony growth. Recently, several independent studies have demon- Identification of the CIP2A-regulated transcriptome M Niemelä et al strated that CIP2A inhibits cellular PP2A activity (Junttila et al, 2007;Chen et al, 2010;Guenebeaud et al, 2010). Moreover, in HeLa cells used for this study, siRNA-mediated CIP2A inhibition induced cellular PP2A activity (data not shown).…”
Section: Cip2a Myc Pp2a and Proliferationmentioning
confidence: 89%
“…These results suggest that MYC contributes to the CIP2A-mediated stimulation of HeLa cell colony growth. Recently, several independent studies have demon- Identification of the CIP2A-regulated transcriptome M Niemelä et al strated that CIP2A inhibits cellular PP2A activity (Junttila et al, 2007;Chen et al, 2010;Guenebeaud et al, 2010). Moreover, in HeLa cells used for this study, siRNA-mediated CIP2A inhibition induced cellular PP2A activity (data not shown).…”
Section: Cip2a Myc Pp2a and Proliferationmentioning
confidence: 89%
“…After 10 min of incubation at 30°C, the malachite dye was added, and free phosphate was measured by optical density at 650 nm. To avoid variability due to differences in the amounts of immunoprecipitated protein between samples, the phosphatase activities were normalized to the amount of PP2A immunoprecipitated, as detected and quantified by immunoblot analysis for each treatment group (17).…”
Section: Methodsmentioning
confidence: 99%
“…The immunoprecipitates were harvested using protein G PLUS-agarose beads (Santa Cruz Biotechnology) that were washed once with regular washing buffer (50 mM Tris-HCl, 100 mM NaCl, 1 mM EDTA, and 0.5% Nonidet P-40), twice with high salt washing buffer (50 mM Tris-HCl, 500 mM NaCl, 1 mM EDTA, and 0.5% Nonidet P-40), and another time with regular washing buffer. Immunoprecipitates were then eluted by boiling the beads for 5 min in SDS/ PAGE sample buffer and characterized by Western blotting with appropriate antibodies (17).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations